Relationships between online motivation, participation and achievement: More complex than you might think - Maggie Hartnett (Journal of Open, Flexible and Distance Learning, 2012)
With the increasing importance and rapid growth of online courses, diversification of the student population, and the growing concern over retention rates, exploration of learner online participation and possible relationships with motivation and achievement behaviour is becoming increasingly relevant in higher education. Previous studies (Gerber, Grundt, & Grote, 2008; Picciano, 2002) have tended to explore links between learner activity and performance in online environments. But the relationships that may exist between motivation and participation (both in terms of quality and quantity of activity) in online contexts are not well understood. Indeed, participation, particularly active participation such as posting messages to online discussions, is frequently used as a proxy for motivation, with more active learners being perceived as more motivated.